2022
DOI: 10.1128/jvi.01011-22
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Preintegration Complex Preferentially Integrates the Viral DNA into Nucleosomes Containing Trimethylated Histone 3-Lysine 36 Modification and Flanking Linker DNA

Abstract: HIV-1 infection is dependent on integration of the viral DNA into the host chromosomes. The preintegration complex (PIC) containing the viral DNA, the virally encoded integrase (IN) enzyme, and other viral/host factors carries out HIV-1 integration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 178 publications
1
8
0
Order By: Relevance
“…Studies of rare people with HIV (PWH) with nonsuppressible HIV-1 viremia (NSV) have shown that the integration sites of the intact producer provirus that are responsible for generating sequencing-matching plasma viruses in the circulation show significant enrichment of activating H3K36 methylation marks [ 34 ]. These findings align with a recent study showing that nucleosomes containing H3K36me3 are preferentially targeted by the HIV-1 preintegration complex [ 35 ]. H3K36 methylation is also found in microglial cells [ 36 ].…”
Section: Epigenetic Control Of Hiv-1 Latencysupporting
confidence: 92%
“…Studies of rare people with HIV (PWH) with nonsuppressible HIV-1 viremia (NSV) have shown that the integration sites of the intact producer provirus that are responsible for generating sequencing-matching plasma viruses in the circulation show significant enrichment of activating H3K36 methylation marks [ 34 ]. These findings align with a recent study showing that nucleosomes containing H3K36me3 are preferentially targeted by the HIV-1 preintegration complex [ 35 ]. H3K36 methylation is also found in microglial cells [ 36 ].…”
Section: Epigenetic Control Of Hiv-1 Latencysupporting
confidence: 92%
“…While the exact inhibition mechanism in the infected cells remains to be fully described, our data show that the selected drugs are good candidates for new antiviral lead compounds and provide a new antiviral precept that may pave the way for further developments of such strategies targeting the integration step. Recent work showed that purified PIC may display distinct behavior that isolated intasome especially in their preference for histone-modified nucleosomes or naked DNA ( 26 ). Thus, testing the selected compounds on these purified complexes may provide additional clues in their action mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Reports on the relationship between histone proteins and viral infections mainly focus on the roles of core histone H2A/B, H3, and H4 or their post-translational modification (PTM) in viral infections, such as Enterovirus 71 (EV71), influenza virus, and human immunodeficiency virus (HIV) [ 25 , 26 , 27 ]. However, there are a few reports on the involvement of linker histones (H1) with viral infection.…”
Section: Discussionmentioning
confidence: 99%